Pengaruh Media Pembelajaran Animasi Powtoon terhadap Hasil Belajar PKn Materi Hak Dan Kewajiban pada Siswa Kelas IV SD - Kasyani Tuti; Mimin Ninawati (Journal of Elementary School (JOES), 2022)
Research on the Effect of Powtoon Animation-Based Digital Learning Media on Civics Learning Outcomes The material on rights and obligations of fourth grade students at SDN Cipayung 03 am aims to determine whether or not the effect of powtoon animation learning media on Civics learning outcomes. The method that the researcher uses is a quantitative experiment with a quasi-experimental design with a pre-test-post-test control group design. The sample in this study amounted to 64 students consisting of the experimental group, namely 32 students in class IV-A and the control group, namely 32 students in class IV-B. The results of the study show that there is a good effect of the powtoon animation learning media on PPKn learning outcomes. The results of this study indicate that the POWTOON animation learning media has an effect on improving student Civics learning outcomes, this is evidenced by the value > with a score of 3.753 > 1.699 so that this study can be said to have a significant influence on student learning outcomes. Keywords: Media Learning, Animation, Civic Right and Obligatitons